Traffic State Comparison of Signalized Intersections Using SIDRA and SYNCHRO Software - Maryam Laith Kareem; Zainab A. Alkaissi (Journal of Engineering and Sustainable Development, 2024)
The number of shopping malls and vehicles in Baghdad has quickly increased along with the city's population. This has resulted in an increase in daily trips, which affects the roadway network's traffic flow and causes congestion, particularly on Al-Mansour Street and Al-Rowad Street near the city center. To determine the best signal time, the 14th Ramadan signalized intersection was evaluated and analyzed using the SIDRA 8.0 and SYNCHRO 11.0 software. First, the findings revealed that the chosen traffic facility is presently experiencing a substantial reduction in service level that is leading to forced conditions (LOS "F"). It is suggested that the cycle time at the intersection of the 14th Ramadan be changed from 240 seconds to 160 seconds and 125 seconds in SIDRA and SYNCHRO, respectively. Signal timings have reduced the delay for the 14th Ramadan intersection (76.8%), thus improving LOS from (F) to (D) for the intersection. The best delays after optimization in SYNCHRO 11.0, however, were 31% reduction with LOS of (E and D). Cycle times have also been lowered for the intersection to 25% as part of the optimum signal timing optimization. In SYNCHRO 11.0, which is better than SIDRA 8.0, the back of the queue has improved at the 14th Ramadan intersection by 33%. However, SYNCHRO has a better representation than SIDRA for current traffic saturation